Inflammasome and Mitophagy Connection in Health and Disease - Yuk, Jae-Min (Int J Mol Sci, 2020)
The inflammasome is a large intracellular protein complex that activates inflammatory caspase-1 and induces the maturation of interleukin (IL)-1β and IL-18. Mitophagy plays an essential role in the maintenance of mitochondrial homeostasis during stress. Previous studies have indicated compelling evidence of the crosstalk between inflammasome and mitophagy. Mitophagy regulation of the inflammasome, or vice versa, is crucial for various biological functions, such as controlling inflammation and metabolism, immune and anti-tumor responses, and pyroptotic cell death. Uncontrolled regulation of the inflammasome often results in pathological inflammation and pyroptosis, and causes a variety of human diseases, including metabolic and inflammatory diseases, infection, and cancer. Here, we discuss how improved understanding of the interactions between inflammasome and mitophagy can lead to novel therapies against various disease pathologies, and how the inflammasome-mitophagy connection is currently being targeted pharmacologically by diverse agents and small molecules. A deeper understanding of the inflammasome-mitophagy connection will provide new insights into human health and disease through the balance between mitochondrial clearance and pathology.